PENGEMBANGAN ENSIKLOPEDIA PERBANYAKAN TANAMAN MELALUI KULTUR JARINGAN SEBAGAI SUMBER BELAJAR TAMBAHAN UNTUK SISWA SMA - Fauziyah Harahap; N Nurliza; Nanda Eska Anugrah Nasution (Universitas Negeri Medan, 2020)
This study aims to determine the feasibility of plant propagation encyclopedias through tissue culture that has been validated by material experts, media experts and by instructional design experts. This research is a Research and Development (R&D). This research model is a 4-D model modified to 3-D consisting of 3 stages, namely defining, designing, and developing. In this study, the instrument used was a questionnaire filled out by material experts, instructional design experts and media experts. From the results of the research that has been done, the results are: (1) Based on the results of the assessment by the material experts, the learning resources developed are stated to be feasible with an average percentage score of 81.3%; (2) Based on the results of the instructional design expert assessment, the learning resources developed were stated to be very feasible with an average percentage of sekor 95.4%; (3) Based on the results of the assessment of media experts, the learning resources developed are stated to be very feasible with an average percentage score of 96%.